Hemorrhoids - Yang, Hyung Kyu (Springer eBooks, 2014)
This book provides up-to-date knowledge on hemorrhoids for proctologists. It covers all aspects, including the history of hemorrhoids, the anatomy of the anal canal, pathophysiology, diagnosis, and treatment. Both conservative treatment approaches and surgical methods are explained with the aid of numerous high-quality illustrations and schematic drawings. Particular attention is paid to lift-up submucosal hemorrhoidectomy, developed by the author by modifying Parks' original method. Additionally, other important techniques proposed by world leaders in the field are described and illustrated. The international trend towards use of day-case hemorrhoidectomy is acknowledged by considering this approach in detail, with discussion of patient preparation, anesthesia, surgical technique, and postoperative management. The treatment of hemorrhoids in a variety of special circumstances is examined, including new trends in PPH. The closing chapter is devoted to the various forms of anesthesia for anal surgery.